2010
DOI: 10.1038/modpathol.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of prolactin receptor expression in colorectal carcinoma and corresponding metastases

Abstract: The role of human prolactin and its receptor, the prolactin receptor, in colorectal cancer is largely unknown. Our study aimed to assess the prevalence of prolactin receptor expression, its association with clinicopathological variables, as well as its prognostic value, comparing results of primary tissues with those of corresponding metastases. In all, 373 primary colorectal cancer and 171 corresponding metastases were evaluated for prolactin receptor expression by immunohistochemistry using a tissue microarr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The role of prolactin in breast cancer has been extensively reviewed by Clevenger et al [105]. Clinical and animal model studies also support a role for autocrine prolactin in prostatic cancer progression [106,107] and elevated prolactin receptor expression is evident in colorectal carcinoma and metastases [108]. These findings can be accommodated in a model of abnormal signaling by these two closely related class-1 cytokine receptors involving excessive activation, particularly of STAT5, but also of STAT3 (Figures 1 & 2) [109][110][111].…”
Section: Altered Gene Expressionmentioning
confidence: 64%
“…The role of prolactin in breast cancer has been extensively reviewed by Clevenger et al [105]. Clinical and animal model studies also support a role for autocrine prolactin in prostatic cancer progression [106,107] and elevated prolactin receptor expression is evident in colorectal carcinoma and metastases [108]. These findings can be accommodated in a model of abnormal signaling by these two closely related class-1 cytokine receptors involving excessive activation, particularly of STAT5, but also of STAT3 (Figures 1 & 2) [109][110][111].…”
Section: Altered Gene Expressionmentioning
confidence: 64%
“…There is evidence suggesting that PRL and PRLR may have a role in human breast cancers as well as prostate, ovarian and colon cancers [8][9][10]14]. We previously demonstrated that increased expression of PRLR is associated with malignant laryngeal tumors [11].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PRLR expression has been found in patients with colorectal cancer, with high concordance between primary tumors and corresponding metastases [42]. These data, combined with animal studies reporting increased metastases with PRL administration [43], suggest that PRL is involved in the development of metastasis and tumor progression.…”
Section: 1 Role Of Prolactin In Regulation Of Breast Cancer Cell Momentioning
confidence: 99%